2015
DOI: 10.7189/jogh.05.020410
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to zinc supplementation guidelines for the treatment of diarrhea among children under–five in Uttar Pradesh, India

Abstract: BackgroundThere is limited evidence on adherence to the recommended dose and duration of zinc supplementation for diarrheal episodes in children under five years of age. In selected districts of Uttar Pradesh, India, we sought to assess adherence to the nationally advised zinc treatment regimen (ie, 10 mg/day for ages 2–6 months and 20 mg/day for ages 7–59 months for 14 days) among caregivers of zinc–prescribed children.MethodsWe identified and conducted follow–up visits to children advised zinc for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…The mean number of days zinc was taken was 11.28±3.81 days in our study while in the study by Lamberti LM et al, it was 10.7 days. 11 The compliance to full zinc therapy of 14 days was 62.14% and similar to our study, Lamberti LM et al, reported that 47.8% continued treatment for the complete 14 days and they also observed that among children receiving zinc syrups and tablets respectively, the age-appropriate dose was received by 30.8% and 67.3%. 11 Ahmed S et al, in their study observed that 62% of the children completed a full 10-day course of zinc treatment by taking one tablet a day that had been completely dissolved in a small amount of water (good compliance).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The mean number of days zinc was taken was 11.28±3.81 days in our study while in the study by Lamberti LM et al, it was 10.7 days. 11 The compliance to full zinc therapy of 14 days was 62.14% and similar to our study, Lamberti LM et al, reported that 47.8% continued treatment for the complete 14 days and they also observed that among children receiving zinc syrups and tablets respectively, the age-appropriate dose was received by 30.8% and 67.3%. 11 Ahmed S et al, in their study observed that 62% of the children completed a full 10-day course of zinc treatment by taking one tablet a day that had been completely dissolved in a small amount of water (good compliance).…”
Section: Discussionsupporting
confidence: 89%
“…11 The compliance to full zinc therapy of 14 days was 62.14% and similar to our study, Lamberti LM et al, reported that 47.8% continued treatment for the complete 14 days and they also observed that among children receiving zinc syrups and tablets respectively, the age-appropriate dose was received by 30.8% and 67.3%. 11 Ahmed S et al, in their study observed that 62% of the children completed a full 10-day course of zinc treatment by taking one tablet a day that had been completely dissolved in a small amount of water (good compliance). 9 There was 63% excess risk for poor compliance to zinc if father stays at home with the family [OR = 1.63 (95%CI; 1.09, 2.46) p = 0.019] in their study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…They are often the first contact point for caregivers for any childhood disease, and parents often seek care only from these practitioners with very little diversion to government service providers . Both ASHAs and RMPs are, therefore, key actors in the early detection and appropriate management of childhood diarrhoea and pneumonia, but the quality of their services is often inadequate because of insufficient training, education, awareness and patient volume .…”
Section: Introductionmentioning
confidence: 99%